Patient-specific estimation of distal lung morphometry using aerosol deposition data - S. G. Karthiga Devi; S. G. Karthiga Devi; Alladi Mohan; Kalawat T.C; Mahesh V. Panchagnula (Frontiers in Physiology)
BackgroundCurrent imaging and diagnostic methods are unable to visualize distal lung beyond the seventh branching generation, despite its critical role in lung function. Inter-individual variability in lung structure influences aerosol deposition within the alveolar region. Understanding an individual’s lung dimensions enables the development of customized treatments. This constitutes the key motivation behind the study.MethodsThis study reports a method to estimate morphometric parameters associated with the distal lung using aerosol deposition characteristics. Aerosol deposition characteristics are measured in a cohort of healthy human subjects using gamma scintigraphy. From this data, differences in the aerosol deposition from subject to subject are quantified. Using a mathematical model of aerosol transport, we demonstrate a novel procedure to estimate patient-specific lung morphometric parameters of the distal generations of the human lung and average alveolar diameter.ResultsMorphometric parameters of the healthy subjects recruited in the study are determined. The lung volumes predicted using the morphometric parameters are unique and different for each subject as expected. The study also predicts the airway diameters and length at every generation for all of the subjects. From the predicted parameters for each of the individual, it can be clearly seen that the lung dimensions vary from individual to individual.ConclusionThe study demonstrates that measurements of aerosol deposition, especially in the distal generations, are a highly sensitive marker for inter-subject variability in lung morphology. The method presented in this study could be packaged into a walk-in lab test, the results from which could help physicians to personalize treatment and pulmonary drug dosage.